High-performance silicon nitride-aluminum nitride ceramic device and 3D printing method thereof

Through multi-material photocuring forming technology, composite silicon nitride ceramics and aluminum nitride ceramics are prepared to produce high-performance silicon nitride-aluminum nitride ceramic devices, which solves the problems of insufficient strength of aluminum nitride ceramics and unsatisfactory thermal conductivity of silicon nitride ceramics in the prior art, and achieves the consideration of high thermal conductivity and mechanical strength.

CN119638439APending Publication Date: 2025-03-18DONGGUAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411844963.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the prior art, the strength of aluminum nitride ceramics is insufficient, while the thermal conductivity of silicon nitride ceramics is not ideal, making it difficult to achieve breakthroughs in the unity of mechanical properties and multiple functions.

Method used

Through multi-material photocuring forming technology, composite silicon nitride ceramics and aluminum nitride ceramics are prepared to produce high-performance silicon nitride-aluminum nitride ceramic devices. The method includes placing a ceramic powder containing a sintering aid and a dispersion medium, adding a photocuring resin plasticizer, a dispersing agent and a photoinitiator, performing photocuring and degreasing and sintering treatment.

Benefits of technology

It achieves the balance between high thermal conductivity and mechanical strength of ceramic devices, solves the shortcomings in strength and thermal conductivity of a single material, and has a wider application prospect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638439A_ABST
    Figure CN119638439A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic 3D printing, in particular to a high-performance silicon nitride-aluminum nitride ceramic device and a 3D printing method thereof.The 3D printing method comprises the following steps that S1, silicon nitride ceramic powder and aluminum nitride ceramic powder are prepared; s2, preparing silicon nitride ceramic slurry and aluminum nitride ceramic slurry; s3, adding the silicon nitride slurry and the aluminum nitride slurry into a slurry cavity of a multi-material photocuring 3D printer, and inputting model information of the silicon nitride-aluminum nitride ceramic device into the printer for photocuring forming; and S4, performing degreasing and sintering treatment on the printed green body to obtain the high-performance silicon nitride-aluminum nitride ceramic device. According to the 3D printing method, the multi-material photocuring forming technology is utilized, composite forming of the silicon nitride ceramic and the aluminum nitride ceramic is achieved, the ceramic device can obtain high heat conductivity, and meanwhile considerable mechanical strength can be guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic 3D printing, and in particular to a high-performance silicon nitride-aluminum nitride ceramic device and a 3D printing method thereof. Background Art

[0002] As an advanced ceramic material, silicon nitride has many excellent properties. It has high strength, high hardness, high fracture toughness, high temperature resistance, wear resistance, corrosion resistance, small thermal expansion coefficient, good thermal shock resistance, etc. Therefore, it is widely used in metallurgy, machinery, automobile, aerospace and other fields. Silicon nitride ceramics have high room temperature bending strength and fracture toughness. Silicon nitride materials have always been considered to have a thermal conductivity of 15-60W·m -1 ·K -1 Silicon nitride ceramics are the lowest thermal conductivity materials among all materials. Although the thermal conductivity of silicon nitride ceramics has been continuously improved in recent years with the continuous efforts of researchers, there is still a big gap with the ideal state.

[0003] Aluminum nitride ceramics are a type of ceramic material commonly used in the electronics industry in recent years. They have a very high thermal conductivity. Theoretically, the thermal conductivity of aluminum nitride can reach 320W·m -1 ·K -1 , which is similar to that of metallic copper. At the same time, it also has the advantages of excellent electrical insulation and thermal expansion performance, so it has become a new generation of ideal electronic packaging materials. The mechanical bending strength of aluminum nitride ceramics is about 350-400MPa, which is significantly lower than that of silicon nitride ceramics.

[0004] Stereolithography is an emerging 3D printing technology that is used in the field of ceramic molding and manufacturing. This technology mainly disperses ceramic powder evenly into a solution to prepare a photosensitive ceramic slurry, which is then cured layer by layer by ultraviolet light irradiation, so that the green body can be quickly formed. After the subsequent degreasing and sintering process, the green body is densified to become a ceramic part with certain mechanical properties. Stereolithography has advantages that traditional molding technologies cannot match. It has a fast molding speed, a very high degree of design freedom, small light source vibration deviation, high resolution, and better molding accuracy than traditional processes. However, the stereolithography of a single material can only enable parts to achieve a single mechanical, optical, thermal, chemical and other properties, and cannot achieve the unity of mechanical properties and multiple functions. Summary of the invention

[0005] In order to overcome the shortcomings and deficiencies in the prior art, an object of the present invention is to provide a high-performance silicon nitride-aluminum nitride ceramic device and a 3D printing method thereof.

[0006] The purpose of the present invention is achieved by the following technical solution: A 3D printing method for high-performance silicon nitride-aluminum nitride ceramic devices, comprising the following steps:

[0007] S1. respectively preparing silicon nitride ceramic powder and aluminum nitride ceramic powder containing a sintering aid and a dispersion medium;

[0008] S2, preparing silicon nitride ceramic slurry containing photocurable resin plasticizer, dispersant and photoinitiator; preparing aluminum nitride ceramic slurry containing photocurable resin plasticizer, dispersant and photoinitiator;

[0009] S3, adding silicon nitride slurry and aluminum nitride slurry into the slurry chamber of the multi-material light-curing 3D printer, and inputting the model information of the silicon nitride-aluminum nitride ceramic device into the printer for light-curing forming;

[0010] S4. After degreasing and sintering the printed body, a high-performance silicon nitride-aluminum nitride ceramic device is obtained.

[0011] The 3D printing method of the present invention utilizes multi-material photocuring forming technology to achieve composite forming of silicon nitride ceramics and aluminum nitride ceramics, which can not only enable the ceramic device to obtain high thermal conductivity, but also ensure considerable mechanical strength, thereby solving the problems of insufficient strength of single-material aluminum nitride ceramics and unsatisfactory thermal conductivity of silicon nitride.

[0012] Preferably, the step S1 specifically includes the following steps:

[0013] S11, preparation of silicon nitride ceramic powder: placing dispersion medium, silicon nitride powder, sintering aid and grinding balls into a ball mill in sequence, and ball milling at a rotation speed of 200-350 rpm for 3-6 hours;

[0014] S12, drying the silicon nitride ceramic powder by a rotary evaporator, and passing through a 50-150 mesh sieve to obtain uniform and highly dispersed silicon nitride ceramic powder;

[0015] S13, preparation of aluminum nitride ceramic powder: placing a dispersion medium, aluminum nitride powder, a sintering aid and grinding balls into a ball mill in sequence, and ball milling at a rotation speed of 200-350 rpm for 3-6 hours;

[0016] S14, drying the aluminum nitride ceramic powder by a rotary evaporator, and passing through a 50-150 mesh sieve to obtain uniform aluminum nitride ceramic powder with high dispersibility.

[0017] Preferably, in the step S11, the amount of silicon nitride powder is 70-100 parts, the amount of sintering aid is 0-10 parts, and the mass ratio of silicon nitride powder to dispersion medium is 1:2.5-3.5; in the step S13, the amount of aluminum nitride powder is 70-100 parts, the amount of sintering aid is 0-10 parts, and the mass ratio of silicon nitride powder to dispersion medium is 1:1.5-2.5; in the steps S11 and S13, the sintering aid is magnesium silicon nitride or rare earth oxide, and the dispersion medium is anhydrous ethanol.

[0018] Preferably, in step S11 and step S13, the sintering aid is a Y2O3-Al2O3-Re2O3 system, wherein Re is a rare earth element other than Y, such as Sc, La, Gd or Sm.

[0019] Preferably, the step S2 specifically includes the following steps:

[0020] S21, preparation of silicon nitride ceramic slurry: placing a photocurable resin, a plasticizer, a dispersant, a photoinitiator, the above silicon nitride ceramic powder and a grinding ball into a ball mill in proportion, and ball milling is performed at room temperature at a ball milling speed of 500-2000 rpm for 5-30 min, and after vacuum degassing, a silicon nitride ceramic slurry with a solid content of 75%-85% is obtained;

[0021] S22. Preparation of aluminum nitride ceramic slurry: Place photocurable resin, plasticizer, dispersant, photoinitiator, the above-mentioned aluminum nitride ceramic powder and grinding balls into a ball mill in proportion, and perform ball milling at room temperature. The ball milling speed is 500-2000rpm, and the ball milling time is 5-30min. After vacuum degassing, aluminum nitride ceramic slurry with a solid content of 75%-85% is obtained.

[0022] The photocurable resin is at least one of ethoxy pentaerythritol tetraacrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, o-phenylphenoxyethyl acrylate and 2-phenoxyethyl acrylate.

[0023] The plasticizer is at least one of dioctyl phthalate, dibutyl phthalate, tributyl citrate, trioctyl citrate and polyethylene glycol.

[0024] The photoinitiator is at least one of bis-2,6-difluoro-3-pyrrolophenyl titanocene, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester, 2-dimethylamino-2-benzyl-1-[4-(4-morpholinyl)phenyl]-1-butanone, and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone.

[0025] The dispersant is at least one of γ-methacryloxypropyltrimethoxysilane, aluminate coupling agent, γ-aminopropyltriethoxysilane, ester-based quaternary ammonium salt and polyethylene glycol octylphenyl ether.

[0026] Preferably, in the step S21, the amount of silicon nitride ceramic powder is 70-95 parts, the amount of photocurable resin is 5-30 parts, the amount of plasticizer is 0.1-10 parts, the amount of dispersant is 0.1-5 parts, and the amount of photoinitiator is 0.1-10 parts; in the step S22, the amount of aluminum nitride ceramic powder is 70-95 parts, the amount of photocurable resin is 5-30 parts, the amount of plasticizer is 0.1-10 parts, the amount of dispersant is 0.1-5 parts, and the amount of photoinitiator is 0.1-10 parts.

[0027] Preferably, the step S3 specifically includes the following steps:

[0028] S31, adding silicon nitride ceramic slurry and aluminum nitride ceramic slurry into two material chambers of a multi-material light-curing 3D printer respectively, and uploading silicon nitride-aluminum nitride ceramic device model information to the printer;

[0029] S32, set the laser power to 10-100mW / cm 2 The printing layer thickness is 10-50μm, the exposure time of each layer is 1-50s, and the silicon nitride-aluminum nitride ceramic device green body is obtained.

[0030] Preferably, the step S4 specifically includes the following steps:

[0031] S41, performing a two-step degreasing treatment on the printed silicon nitride-aluminum nitride ceramic green body, firstly placing it in a vacuum / atmosphere environment for decomposition treatment, the decomposition temperature is 400-800° C., and the insulation time is 1-5 hours; then the decomposed green body is placed in an air environment for decarburization, the decarburization temperature is 400-800° C., and the insulation time is 1-5 hours;

[0032] S42, sintering the degreased sample at a sintering temperature of 1700-1900° C., a heat preservation time of 1-6 hours, and an atmosphere pressure of 0.1-5 MPa to obtain the high-performance silicon nitride-aluminum nitride ceramic device.

[0033] The sintering process can be gas pressure sintering, atmosphere sintering or hot isostatic pressing.

[0034] Another object of the present invention is achieved through the following technical solution: a high-performance silicon nitride-aluminum nitride ceramic device, wherein the high-performance silicon nitride-aluminum nitride ceramic device is manufactured according to the above-mentioned 3D printing method.

[0035] Preferably, the high-performance silicon nitride-aluminum nitride ceramic device comprises a support member made of silicon nitride ceramic and a heat-conducting member made of aluminum nitride ceramic that penetrates both ends of the support member and forms a passage; the strength of the high-performance silicon nitride-aluminum nitride ceramic device is 800-900 MPa, and the thermal conductivity is 110-130 W·m -1 ·K -1 .

[0036] The beneficial effect of the present invention is that the 3D printing method of the present invention utilizes multi-material photocuring forming technology to realize the composite forming of silicon nitride ceramics and aluminum nitride ceramics, which can not only enable the ceramic device to obtain high thermal conductivity, but also ensure considerable mechanical strength, thereby solving the problem of insufficient strength of single-material aluminum nitride ceramics and unsatisfactory thermal conductivity of silicon nitride.

[0037] The 3D printing method of the present invention can prepare silicon nitride and aluminum nitride ceramics by integrated forming, and can realize the preparation of components with complex shapes.

[0038] The high-performance silicon nitride-aluminum nitride ceramic device formula of the present invention has obvious performance advantages. Compared with single silicon nitride ceramic parts and aluminum nitride ceramic parts, the high-performance silicon nitride-aluminum nitride ceramic device has the high thermal conductivity of aluminum nitride while taking into account the high strength performance of silicon nitride, thereby solving the problems of insufficient thermal conductivity of silicon nitride ceramics and substandard strength of aluminum nitride ceramics. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 Schematic diagram of the process of multi-material photocuring 3D printing preparation of high-performance silicon nitride-aluminum nitride ceramic devices of the present invention.

[0040] Figure 2 Schematic diagram of printing silicon nitride-aluminum nitride ceramic devices by the multi-material light-curing 3D printer of the present invention.

[0041] Figure 3 It is a model of the high performance silicon nitride-aluminum nitride ceramic device of the present invention.

[0042] Figure 4This is another model of the high performance silicon nitride-aluminum nitride ceramic device of the present invention. DETAILED DESCRIPTION

[0043] In order to facilitate the understanding of those skilled in the art, the following embodiments and attached Figure 1-4 The present invention is further described, and the contents mentioned in the implementation modes are not intended to limit the present invention.

[0044] Example 1

[0045] See Figure 1 , a 3D printing method for high-performance silicon nitride-aluminum nitride ceramic devices, comprising the following steps:

[0046] S1. respectively preparing silicon nitride ceramic powder and aluminum nitride ceramic powder containing a sintering aid and a dispersion medium;

[0047] S2, preparing silicon nitride ceramic slurry containing photocurable resin plasticizer, dispersant and photoinitiator; preparing aluminum nitride ceramic slurry containing photocurable resin plasticizer, dispersant and photoinitiator;

[0048] S3, adding silicon nitride slurry and aluminum nitride slurry into the slurry chamber of the multi-material light-curing 3D printer, and inputting the model information of the silicon nitride-aluminum nitride ceramic device into the printer for light-curing forming;

[0049] S4. After degreasing and sintering the printed body, a high-performance silicon nitride-aluminum nitride ceramic device is obtained.

[0050] The step S1 specifically includes the following steps:

[0051] S11, preparation of silicon nitride ceramic powder: placing dispersion medium, silicon nitride powder, sintering aid and grinding balls into a ball mill in sequence, and ball milling at a rotation speed of 200 rpm for 6 hours;

[0052] S12, drying the silicon nitride ceramic powder by a rotary evaporator, and passing through a 50-mesh sieve to obtain uniform and highly dispersed silicon nitride ceramic powder;

[0053] S13, preparation of aluminum nitride ceramic powder: placing dispersion medium, aluminum nitride powder, sintering aid and grinding balls into a ball mill in sequence, and ball milling at a rotation speed of 200 rpm for 6 hours;

[0054] S14, drying the aluminum nitride ceramic powder by a rotary evaporator, and passing through a 50-mesh sieve to obtain uniform aluminum nitride ceramic powder with high dispersibility.

[0055] In the step S11, the amount of silicon nitride powder is 70 parts, the amount of sintering aid is 1 part, and the mass ratio of silicon nitride powder to dispersion medium is 1:2.5; in the step S13, the amount of aluminum nitride powder is 70 parts, the amount of sintering aid is 1 part, and the mass ratio of silicon nitride powder to dispersion medium is 1:1.5; in the steps S11 and S13, the sintering aid is scandium oxide, and the dispersion medium is anhydrous ethanol.

[0056] The step S2 specifically includes the following steps:

[0057] S21, preparation of silicon nitride ceramic slurry: placing a photocurable resin, a plasticizer, a dispersant, a photoinitiator, the silicon nitride ceramic powder and a grinding ball into a ball mill in proportion, and performing ball milling at room temperature, with a ball milling speed of 500 rpm and a ball milling time of 30 min, and obtaining a silicon nitride ceramic slurry with a solid content of 75% after vacuum degassing;

[0058] S22. Preparation of aluminum nitride ceramic slurry: Place photocurable resin, plasticizer, dispersant, photoinitiator, the above-mentioned aluminum nitride ceramic powder and grinding balls into a ball mill in proportion, and perform ball milling at room temperature with a ball milling speed of 500 rpm and a ball milling time of 30 min. After vacuum degassing, obtain aluminum nitride ceramic slurry with a solid content of 75%.

[0059] In the step S21, the amount of silicon nitride ceramic powder is 70 parts, the amount of photocurable resin is 5 parts, the amount of plasticizer is 1 part, the amount of dispersant is 1 part, and the amount of photoinitiator is 1 part; in the step S22, the amount of aluminum nitride ceramic powder is 70 parts, the amount of photocurable resin is 5 parts, the amount of plasticizer is 1 part, the amount of dispersant is 1 part, and the amount of photoinitiator is 1 part.

[0060] The photocurable resin is ethoxy pentaerythritol tetraacrylate.

[0061] The plasticizer is dibutyl phthalate.

[0062] The photoinitiator is bis-2,6-difluoro-3-pyrrophenyl titanocene.

[0063] The dispersant is γ-methacryloxypropyltrimethoxysilane.

[0064] The step S3 specifically includes the following steps:

[0065] S31, adding silicon nitride ceramic slurry and aluminum nitride ceramic slurry into two material chambers of a multi-material light-curing 3D printer respectively, and uploading silicon nitride-aluminum nitride ceramic device model information to the printer;

[0066] S32, set the laser power to 10mW / cm 2 The printing layer thickness is 10 μm, the exposure time of each layer is 30 s, and the silicon nitride-aluminum nitride ceramic device green body is obtained.

[0067] Specifically, Figure 2 As shown, silicon nitride ceramic slurry and aluminum nitride ceramic slurry are respectively injected into two material chambers of a multi-material photocuring printer. First, the curing platform is exposed and cured to a certain layer thickness in chamber 1 according to its slice image, and then transferred to chamber 2 to cure the corresponding layer thickness. This cycle is repeated to finally obtain a silicon nitride-aluminum nitride ceramic device green body.

[0068] The step S4 specifically includes the following steps:

[0069] S41, performing a two-step degreasing treatment on the printed silicon nitride-aluminum nitride ceramic green body, firstly placing it in a vacuum / atmosphere environment for decomposition treatment, the decomposition temperature is 400° C., and the holding time is 5 hours; then the decomposed green body is placed in an air environment for decarburization, the decarburization temperature is 400° C., and the holding time is 5 hours;

[0070] S42, subjecting the degreased sample to gas pressure sintering treatment, with a sintering temperature of 1700° C., a heat preservation time of 6 hours, and an atmosphere pressure of 1 MPa, to obtain the high-performance silicon nitride-aluminum nitride ceramic device.

[0071] A high-performance silicon nitride-aluminum nitride ceramic device is manufactured according to the above-mentioned 3D printing method.

[0072] Example 2

[0073] The difference between this embodiment and the above-mentioned embodiment 1 is that:

[0074] S11, preparation of silicon nitride ceramic powder: put the dispersion medium, silicon nitride powder, sintering aid and grinding balls into a ball mill in sequence, and ball mill at a rotation speed of 250 rpm for 5 hours;

[0075] S12, drying the silicon nitride ceramic powder by a rotary evaporator, and passing through an 80-mesh sieve to obtain uniform and highly dispersed silicon nitride ceramic powder;

[0076] S13, preparation of aluminum nitride ceramic powder: placing dispersion medium, aluminum nitride powder, sintering aid and grinding balls into a ball mill in sequence, and ball milling at a rotation speed of 250 rpm for 5 hours;

[0077] S14, drying the aluminum nitride ceramic powder by a rotary evaporator, and passing it through an 80-mesh sieve to obtain uniform aluminum nitride ceramic powder with high dispersibility.

[0078] In the step S11, the amount of silicon nitride powder is 80 parts, the amount of sintering aid is 3 parts, and the mass ratio of silicon nitride powder to dispersion medium is 1:2.8; in the step S13, the amount of aluminum nitride powder is 80 parts, the amount of sintering aid is 3 parts, and the mass ratio of silicon nitride powder to dispersion medium is 1:1.8; in the steps S11 and S13, the sintering aid is lanthanum oxide, and the dispersion medium is anhydrous ethanol.

[0079] The step S2 specifically includes the following steps:

[0080] S21, preparation of silicon nitride ceramic slurry: placing a photocurable resin, a plasticizer, a dispersant, a photoinitiator, the above silicon nitride ceramic powder and a grinding ball into a ball mill in proportion, and performing ball milling at room temperature, with a ball milling speed of 1000 rpm and a ball milling time of 25 min, and obtaining a silicon nitride ceramic slurry with a solid content of 78% after vacuum degassing;

[0081] S22. Preparation of aluminum nitride ceramic slurry: Place photocurable resin, plasticizer, dispersant, photoinitiator, the above-mentioned aluminum nitride ceramic powder and grinding balls into a ball mill in proportion, and perform ball milling at room temperature. The ball milling speed is 1000 rpm, and the ball milling time is 25 min. After vacuum degassing, aluminum nitride ceramic slurry with a solid content of 78% is obtained.

[0082] In the step S21, the amount of silicon nitride ceramic powder is 75 parts, the amount of photocurable resin is 10 parts, the amount of plasticizer is 3 parts, the amount of dispersant is 2 parts, and the amount of photoinitiator is 3 parts; in the step S22, the amount of aluminum nitride ceramic powder is 75 parts, the amount of photocurable resin is 10 parts, the amount of plasticizer is 3 parts, the amount of dispersant is 2 parts, and the amount of photoinitiator is 3 parts.

[0083] The photocurable resin is 1,6-hexanediol diacrylate.

[0084] The plasticizer is tributyl citrate.

[0085] The photoinitiator is 1-hydroxycyclohexyl phenyl ketone.

[0086] The dispersant is an aluminate coupling agent.

[0087] The step S3 specifically includes the following steps:

[0088] S31, adding silicon nitride ceramic slurry and aluminum nitride ceramic slurry into two material chambers of a multi-material light-curing 3D printer respectively, and uploading silicon nitride-aluminum nitride ceramic device model information to the printer;

[0089] S32, set the laser power to 30mW / cm 2The printing layer thickness is 20 μm, the exposure time of each layer is 20 s, and the silicon nitride-aluminum nitride ceramic device green body is obtained.

[0090] The step S4 specifically includes the following steps:

[0091] S41, performing a two-step degreasing treatment on the printed silicon nitride-aluminum nitride ceramic green body, firstly placing it in a vacuum / atmosphere environment for decomposition treatment, the decomposition temperature is 500° C., and the holding time is 4 hours; then the decomposed green body is placed in an air environment for decarburization, the decarburization temperature is 500° C., and the holding time is 4 hours;

[0092] S42, subjecting the degreased sample to atmosphere sintering treatment, with a sintering temperature of 1750° C., a heat preservation time of 5 hours, and an atmosphere pressure of 2 MPa, to obtain the high-performance silicon nitride-aluminum nitride ceramic device.

[0093] A high-performance silicon nitride-aluminum nitride ceramic device is manufactured according to the above-mentioned 3D printing method.

[0094] Example 3

[0095] The difference between this embodiment and the above-mentioned embodiment 1 is that:

[0096] S11, preparation of silicon nitride ceramic powder: put the dispersion medium, silicon nitride powder, sintering aid and grinding balls into a ball mill in sequence, and mill at a rotation speed of 350 rpm for 4 hours;

[0097] S12, drying the silicon nitride ceramic powder by a rotary evaporator, and passing through a 100-mesh sieve to obtain uniform and highly dispersed silicon nitride ceramic powder;

[0098] S13, preparation of aluminum nitride ceramic powder: placing dispersion medium, aluminum nitride powder, sintering aid and grinding balls into a ball mill in sequence, and ball milling at a rotation speed of 350 rpm for 4 hours;

[0099] S14, drying the aluminum nitride ceramic powder by a rotary evaporator, and passing through a 100-mesh sieve to obtain uniform aluminum nitride ceramic powder with high dispersibility.

[0100] In the step S11, the amount of silicon nitride powder is 94 parts, the amount of sintering aid is 6 parts, and the mass ratio of silicon nitride powder to dispersion medium is 1:3; in the step S13, the amount of aluminum nitride powder is 94 parts, the amount of sintering aid is 6 parts, and the mass ratio of silicon nitride powder to dispersion medium is 1:2; in the steps S11 and S13, the sintering aid is a mixture of yttrium oxide and magnesium silicon nitride in a weight ratio of 1-5, and the dispersion medium is anhydrous ethanol.

[0101] The step S2 specifically includes the following steps:

[0102] S21, preparation of silicon nitride ceramic slurry: placing a photocurable resin, a plasticizer, a dispersant, a photoinitiator, the above silicon nitride ceramic powder and a grinding ball into a ball mill in proportion, and ball milling is performed at room temperature at a ball milling speed of 1500 rpm for 20 min, and after vacuum degassing, a silicon nitride ceramic slurry with a solid content of 80% is obtained;

[0103] S22. Preparation of aluminum nitride ceramic slurry: Place photocurable resin, plasticizer, dispersant, photoinitiator, the above-mentioned aluminum nitride ceramic powder and grinding balls into a ball mill in proportion, and perform ball milling at room temperature with a ball milling speed of 1500 rpm and a ball milling time of 20 min. After vacuum degassing, aluminum nitride ceramic slurry with a solid content of 80% is obtained.

[0104] In the step S21, the amount of silicon nitride ceramic powder is 80 parts, the amount of photocurable resin is 15 parts, the amount of plasticizer is 5 parts, the amount of dispersant is 3 parts, and the amount of photoinitiator is 5 parts; in the step S22, the amount of aluminum nitride ceramic powder is 80 parts, the amount of photocurable resin is 16 parts, the amount of plasticizer is 5 parts, the amount of dispersant is 3 parts, and the amount of photoinitiator is 5 parts.

[0105] The photocurable resin is composed of ethoxy pentaerythritol tetraacrylate and 1,6-hexanediol diacrylate in a weight ratio of 3:4.

[0106] The plasticizer is dioctyl phthalate.

[0107] The photoinitiator is 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone.

[0108] The dispersant is γ-aminopropyltriethoxysilane.

[0109] The step S3 specifically includes the following steps:

[0110] S31, adding silicon nitride ceramic slurry and aluminum nitride ceramic slurry into two material chambers of a multi-material light-curing 3D printer respectively, and uploading silicon nitride-aluminum nitride ceramic device model information to the printer;

[0111] S32, set the laser power to 60mW / cm 2 The printing layer thickness is 30 μm, the exposure time of each layer is 15 s, and the silicon nitride-aluminum nitride ceramic device green body is obtained.

[0112] The step S4 specifically includes the following steps:

[0113] S41, performing a two-step degreasing treatment on the printed silicon nitride-aluminum nitride ceramic green body, firstly placing it in a vacuum / atmosphere environment for decomposition treatment, the decomposition temperature is 600°C, and the holding time is 3h; then the decomposed green body is placed in an air environment for decarburization, the decarburization temperature is 600°C, and the holding time is 3h;

[0114] S42, subjecting the degreased sample to gas pressure sintering treatment, with a sintering temperature of 1800° C., a heat preservation time of 4 hours, and an atmosphere pressure of 3 MPa, to obtain the high-performance silicon nitride-aluminum nitride ceramic device.

[0115] A high-performance silicon nitride-aluminum nitride ceramic device is manufactured according to the above-mentioned 3D printing method.

[0116] Example 4

[0117] The difference between this embodiment and the above-mentioned embodiment 1 is that:

[0118] S11, preparation of silicon nitride ceramic powder: put the dispersion medium, silicon nitride powder, sintering aid and grinding balls into a ball mill in sequence, and mill at a rotation speed of 350 rpm for 3 hours;

[0119] S12, drying the silicon nitride ceramic powder by a rotary evaporator, and passing through a 120-mesh sieve to obtain uniform and highly dispersed silicon nitride ceramic powder;

[0120] S13, preparation of aluminum nitride ceramic powder: placing dispersion medium, aluminum nitride powder, sintering aid and grinding balls into a ball mill in sequence, and ball milling at a rotation speed of 350 rpm for 3 hours;

[0121] S14, drying the aluminum nitride ceramic powder by a rotary evaporator, and passing it through a 120-mesh sieve to obtain uniform aluminum nitride ceramic powder with high dispersibility.

[0122] In the step S11, the amount of silicon nitride powder is 90 parts, the amount of sintering aid is 8 parts, and the mass ratio of silicon nitride powder to dispersion medium is 1:3.2; in the step S13, the amount of aluminum nitride powder is 90 parts, the amount of sintering aid is 8 parts, and the mass ratio of silicon nitride powder to dispersion medium is 1:2.2; in the steps S11 and S13, the sintering aid is gadolinium oxide, and the dispersion medium is anhydrous ethanol.

[0123] The step S2 specifically includes the following steps:

[0124] S21, preparation of silicon nitride ceramic slurry: placing a photocurable resin, a plasticizer, a dispersant, a photoinitiator, the above silicon nitride ceramic powder and a grinding ball into a ball mill in proportion, and performing ball milling at room temperature, with a ball milling speed of 1800 rpm and a ball milling time of 10 min, and obtaining a silicon nitride ceramic slurry with a solid content of 82% after vacuum degassing;

[0125] S22. Preparation of aluminum nitride ceramic slurry: Place photocurable resin, plasticizer, dispersant, photoinitiator, the above-mentioned aluminum nitride ceramic powder and grinding balls into a ball mill in proportion, and perform ball milling at room temperature with a ball mill speed of 1800 rpm and a ball milling time of 10 min. After vacuum degassing, aluminum nitride ceramic slurry with a solid content of 82% is obtained.

[0126] In the step S21, the amount of silicon nitride ceramic powder is 85 parts, the amount of photocurable resin is 20 parts, the amount of plasticizer is 8 parts, the amount of dispersant is 4 parts, and the amount of photoinitiator is 8 parts; in the step S22, the amount of aluminum nitride ceramic powder is 85 parts, the amount of photocurable resin is 20 parts, the amount of plasticizer is 8 parts, the amount of dispersant is 4 parts, and the amount of photoinitiator is 8 parts.

[0127] The photocurable resin is trimethylolpropane triacrylate.

[0128] The plasticizer is trioctyl citrate.

[0129] The photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

[0130] The dispersant is an ester-based quaternary ammonium salt.

[0131] The step S3 specifically includes the following steps:

[0132] S31, adding silicon nitride ceramic slurry and aluminum nitride ceramic slurry into two material chambers of a multi-material light-curing 3D printer respectively, and uploading silicon nitride-aluminum nitride ceramic device model information to the printer;

[0133] S32, set the laser power to 80mW / cm 2 The printing layer thickness is 40 μm, the exposure time of each layer is 10 s, and the silicon nitride-aluminum nitride ceramic device green body is obtained.

[0134] The step S4 specifically includes the following steps:

[0135] S41, performing a two-step degreasing treatment on the printed silicon nitride-aluminum nitride ceramic green body, firstly placing it in a vacuum / atmosphere environment for decomposition treatment, the decomposition temperature is 700°C, and the holding time is 2h; then the decomposed green body is placed in an air environment for decarburization, the decarburization temperature is 700°C, and the holding time is 2h;

[0136] S42, subjecting the degreased sample to atmosphere sintering treatment, with a sintering temperature of 1850° C., a heat preservation time of 3 hours, and an atmosphere pressure of 4 MPa, to obtain the high-performance silicon nitride-aluminum nitride ceramic device.

[0137] A high-performance silicon nitride-aluminum nitride ceramic device is manufactured according to the above-mentioned 3D printing method.

[0138] Example 5

[0139] The difference between this embodiment and the above-mentioned embodiment 1 is that:

[0140] S11, preparation of silicon nitride ceramic powder: put the dispersion medium, silicon nitride powder, sintering aid and grinding balls into a ball mill in sequence, and mill at a rotation speed of 300 rpm for 4 hours;

[0141] S12, drying the silicon nitride ceramic powder by a rotary evaporator, and passing through a 150-mesh sieve to obtain uniform and highly dispersed silicon nitride ceramic powder;

[0142] S13, preparation of aluminum nitride ceramic powder: placing dispersion medium, aluminum nitride powder, sintering aid and grinding balls into a ball mill in sequence, and ball milling at a rotation speed of 300 rpm for 4 hours;

[0143] S14, drying the aluminum nitride ceramic powder by a rotary evaporator, and passing through a 150-mesh sieve to obtain uniform aluminum nitride ceramic powder with high dispersibility.

[0144] In the step S11, the amount of silicon nitride powder is 100 parts, the amount of sintering aid is 10 parts, and the mass ratio of silicon nitride powder to dispersion medium is 1:3.5; in the step S13, the amount of aluminum nitride powder is 100 parts, the amount of sintering aid is 10 parts, and the mass ratio of silicon nitride powder to dispersion medium is 1:2.5; in the steps S11 and S13, the sintering aid is samarium oxide, and the dispersion medium is anhydrous ethanol.

[0145] The step S2 specifically includes the following steps:

[0146] S21, preparation of silicon nitride ceramic slurry: placing a photocurable resin, a plasticizer, a dispersant, a photoinitiator, the silicon nitride ceramic powder and a grinding ball into a ball mill in proportion, and performing ball milling at room temperature, with a ball milling speed of 2000 rpm and a ball milling time of 5 min, and obtaining a silicon nitride ceramic slurry with a solid content of 85% after vacuum degassing;

[0147] S22. Preparation of aluminum nitride ceramic slurry: Place photocurable resin, plasticizer, dispersant, photoinitiator, the above-mentioned aluminum nitride ceramic powder and grinding balls into a ball mill in proportion, and perform ball milling at room temperature with a ball mill speed of 2000 rpm and a ball milling time of 5 min. After vacuum degassing, obtain aluminum nitride ceramic slurry with a solid content of 85%.

[0148] In the step S21, the amount of silicon nitride ceramic powder is 95 parts, the amount of photocurable resin is 30 parts, the amount of plasticizer is 10 parts, the amount of dispersant is 5 parts, and the amount of photoinitiator is 10 parts; in the step S22, the amount of aluminum nitride ceramic powder is 95 parts, the amount of photocurable resin is 30 parts, the amount of plasticizer is 10 parts, the amount of dispersant is 5 parts, and the amount of photoinitiator is 10 parts.

[0149] The photocurable resin is composed of o-phenylphenoxyethyl acrylate and 2-phenoxyethyl acrylate in a weight ratio of 2:1.

[0150] The plasticizer is polyethylene glycol.

[0151] The photoinitiator is ethyl 2,4,6-trimethylbenzoylphenylphosphonate.

[0152] The dispersant is polyethylene glycol octyl phenyl ether.

[0153] The step S3 specifically includes the following steps:

[0154] S31, adding silicon nitride ceramic slurry and aluminum nitride ceramic slurry into two material chambers of a multi-material light-curing 3D printer respectively, and uploading silicon nitride-aluminum nitride ceramic device model information to the printer;

[0155] S32, set the laser power to 100mW / cm 2 The printing layer thickness is 50 μm, the exposure time of each layer is 5 s, and the silicon nitride-aluminum nitride ceramic device green body is obtained.

[0156] The step S4 specifically includes the following steps:

[0157] S41, performing a two-step degreasing treatment on the printed silicon nitride-aluminum nitride ceramic green body, firstly placing it in a vacuum / atmosphere environment for decomposition treatment, the decomposition temperature is 800° C., and the holding time is 1 hour; then the decomposed green body is placed in an air environment for decarburization, the decarburization temperature is 800° C., and the holding time is 1 hour;

[0158] S42, subjecting the degreased sample to gas pressure sintering treatment, with a sintering temperature of 1900° C., a heat preservation time of 1 h, and an atmosphere pressure of 5 MPa, to obtain the high-performance silicon nitride-aluminum nitride ceramic device.

[0159] A high-performance silicon nitride-aluminum nitride ceramic device is manufactured according to the above-mentioned 3D printing method.

[0160] The high-performance silicon nitride-aluminum nitride ceramic device prepared by the present invention comprises a support member composed of silicon nitride ceramic and a heat-conducting member composed of aluminum nitride ceramic that penetrates both ends of the support member and forms a passage; Figure 3-4 As shown, aluminum nitride ceramics form passages at both ends of the device to improve the thermal conductivity of the device, and silicon nitride ceramics play a supporting role in the device to enhance the strength of the device.

[0161] The performance test results of the high-performance silicon nitride-aluminum nitride ceramic device prepared by the present invention are as follows:

[0162] Test items Strength (MPa) <![CDATA[Thermal conductivity (W·m -1 ·K -1 )]]> Example 1 821 115 Example 2 847 121 Example 3 893 128 Example 4 876 126 Example 5 854 123

[0163] As can be seen from the above table, the strength of the high-performance silicon nitride-aluminum nitride ceramic device prepared by the present invention can reach 800-900MPa, and the thermal conductivity can reach 110-130W·m -1 ·K -1 .

[0164] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. A 3D printing method for high-performance silicon nitride-aluminum nitride ceramic devices, characterized in that: The steps include: S1. respectively preparing silicon nitride ceramic powder and aluminum nitride ceramic powder containing a sintering aid and a dispersion medium; S2, preparing silicon nitride ceramic slurry containing photocurable resin plasticizer, dispersant and photoinitiator; preparing aluminum nitride ceramic slurry containing photocurable resin plasticizer, dispersant and photoinitiator; S3, adding silicon nitride slurry and aluminum nitride slurry into the slurry chamber of the multi-material light-curing 3D printer, and inputting the model information of the silicon nitride-aluminum nitride ceramic device into the printer for light-curing forming; S4. After degreasing and sintering the printed body, a high-performance silicon nitride-aluminum nitride ceramic device is obtained.

2. A 3D printing method for a high-performance silicon nitride-aluminum nitride ceramic device according to claim 1, characterized in that: The step S1 specifically includes the following steps: S11, preparation of silicon nitride ceramic powder: placing dispersion medium, silicon nitride powder, sintering aid and grinding balls into a ball mill in sequence, and ball milling at a rotation speed of 200-350 rpm for 3-6 hours; S12, drying the silicon nitride ceramic powder by a rotary evaporator, and passing through a 50-150 mesh sieve to obtain uniform and highly dispersed silicon nitride ceramic powder; S13, preparation of aluminum nitride ceramic powder: placing a dispersion medium, aluminum nitride powder, a sintering aid and grinding balls into a ball mill in sequence, and ball milling at a rotation speed of 200-350 rpm for 3-6 hours; S14, drying the aluminum nitride ceramic powder by a rotary evaporator, and passing through a 50-150 mesh sieve to obtain uniform aluminum nitride ceramic powder with high dispersibility.

3. The 3D printing method of a high-performance silicon nitride-aluminum nitride ceramic device according to claim 2, characterized in that: In the step S11, the amount of silicon nitride powder is 70-100 parts, the amount of sintering aid is 0-10 parts, and the mass ratio of silicon nitride powder to dispersion medium is 1:2.5-3.5; in the step S13, the amount of aluminum nitride powder is 70-100 parts, the amount of sintering aid is 0-10 parts, and the mass ratio of silicon nitride powder to dispersion medium is 1:1.5-2.5; in the steps S11 and S13, the sintering aid is magnesium silicon nitride or rare earth oxide, and the dispersion medium is anhydrous ethanol.

4. The 3D printing method of a high-performance silicon nitride-aluminum nitride ceramic device according to claim 2, characterized in that: In the step S11 and the step S13, the sintering aid is a Y2O3-Al2O3-Re2O3 system, wherein Re is a rare earth element other than Y.

5. The 3D printing method of a high-performance silicon nitride-aluminum nitride ceramic device according to claim 1, characterized in that: The step S2 specifically includes the following steps: S21, preparation of silicon nitride ceramic slurry: placing a photocurable resin, a plasticizer, a dispersant, a photoinitiator, the above silicon nitride ceramic powder and a grinding ball into a ball mill in proportion, and ball milling is performed at room temperature at a ball milling speed of 500-2000 rpm for 5-30 min, and after vacuum degassing, a silicon nitride ceramic slurry with a solid content of 75%-85% is obtained; S22. Preparation of aluminum nitride ceramic slurry: Place photocurable resin, plasticizer, dispersant, photoinitiator, the above-mentioned aluminum nitride ceramic powder and grinding balls into a ball mill in proportion, and perform ball milling at room temperature. The ball milling speed is 500-2000rpm, and the ball milling time is 5-30min. After vacuum degassing, aluminum nitride ceramic slurry with a solid content of 75%-85% is obtained.

6. The 3D printing method of a high-performance silicon nitride-aluminum nitride ceramic device according to claim 5, characterized in that: In the step S21, the amount of silicon nitride ceramic powder is 70-95 parts, the amount of photocurable resin is 5-30 parts, the amount of plasticizer is 0.1-10 parts, the amount of dispersant is 0.1-5 parts, and the amount of photoinitiator is 0.1-10 parts; in the step S22, the amount of aluminum nitride ceramic powder is 70-95 parts, the amount of photocurable resin is 5-30 parts, the amount of plasticizer is 0.1-10 parts, the amount of dispersant is 0.1-5 parts, and the amount of photoinitiator is 0.1-10 parts.

7. The 3D printing method of a high-performance silicon nitride-aluminum nitride ceramic device according to claim 1, characterized in that: The step S3 specifically includes the following steps: S31, adding silicon nitride ceramic slurry and aluminum nitride ceramic slurry into two material chambers of a multi-material light-curing 3D printer respectively, and uploading silicon nitride-aluminum nitride ceramic device model information to the printer; S32, set the laser power to 10-100mW / cm 2 The printing layer thickness is 10-50μm, the exposure time of each layer is 1-50s, and the silicon nitride-aluminum nitride ceramic device green body is obtained.

8. The 3D printing method of a high-performance silicon nitride-aluminum nitride ceramic device according to claim 1, characterized in that: The step S4 specifically includes the following steps: S41, performing a two-step degreasing treatment on the printed silicon nitride-aluminum nitride ceramic green body, firstly placing it in a vacuum / atmosphere environment for decomposition treatment, the decomposition temperature is 400-800° C., and the insulation time is 1-5 hours; then the decomposed green body is placed in an air environment for decarburization, the decarburization temperature is 400-800° C., and the insulation time is 1-5 hours; S42, sintering the degreased sample at a sintering temperature of 1700-1900° C., a heat preservation time of 1-6 hours, and an atmosphere pressure of 0.1-5 MPa to obtain the high-performance silicon nitride-aluminum nitride ceramic device.

9. A high performance silicon nitride-aluminum nitride ceramic device, characterized in that: The high-performance silicon nitride-aluminum nitride ceramic device is manufactured according to the 3D printing method according to any one of claims 1-8.

10. A high performance silicon nitride-aluminum nitride ceramic device according to claim 9, characterized in that: The high-performance silicon nitride-aluminum nitride ceramic device comprises a support member made of silicon nitride ceramic and a heat-conducting member made of aluminum nitride ceramic that penetrates both ends of the support member and forms a passage; the high-performance silicon nitride-aluminum nitride ceramic device has a strength of 800-900 MPa and a thermal conductivity of 110-130 W·m -1 ·K -1 .